Medical education for undergraduate research: Proposals from the experience of two national student conferences of the Universidad de Valparaíso - Carlos Cabrera-Ubilla; Sebastián Almarza Santander; Marcelo Arancibia; María Elizabeth Guerra-Zúñiga (Medwave, 2024)
Introduction Scientific research promotes the development of essential skills for medical practice. However, student participation in research projects is low, with multiple limitations and students' perceptions of deficient research skills. This study aims to describe the organization of the two medical student conferences held by the Scientific Society of Medical Students of the Universidad de Valparaíso and to analyze the papers presented. Finally, we make recommendations for promoting scientific research among medical students.